Особливості конституційного статусу особи в монархіях Арабського Сходу - Гришко, Л. М.; Gryshko, L. M.; ORCID: http://orcid.org/0000-0003-0347-1118 (Право і безпека. – 2017. – № 3 (66). – С. 21-26, 2017)
На основі чинних конституцій монархій Арабського Сходу та політико-правової практики продемонстровано особливості закріплення прав, свобод та обов’язків громадян (підданих). Зроблено висновок про те, що конституційний статус особи в цих державах лише формально виглядає суттєво модернізованим і демократизованим, проте фактично не є таким. Водночас наведено приклади діяльності органів конституційної юстиції, що свідчать про суттєві зміни в розумінні закріплених принципів, прав та свобод.

The author of the article observes that the issues of consolidating Islam as a state religion and the main source of legislation in combination with the fixing at the constitutional level of the “Western” concept of human rights is largely out of the question. Since the traditional norms of the state religion – Islam are seriously influenced by the constitutional rights and freedoms of the monarchy of the Arab East, it is unequivocally possible to affirm the purely “European modernization” in this area. Considering this, one should pay attention to a number of features of the constitutional status of a person in these states. On the basis of the current constitutions of the monarchies of the Arab East and political and legal practice the author has demonstrated the features of consolidation of the rights, freedoms and duties of citizens (subjects). It has been concluded that the peculiarities of the constitutional status of a person in the monarchies of the Arab East are that the existing constitutions have consolidated a wide range of principles, rights, freedoms that often go beyond Shariah, but their interpretation is often limited to Islam. The constitutional status appears formally to be substantially upgraded and democratized, but in fact it is not. At the same time, the author of the article provides examples of the activities of the agencies of constitutional justice, which testify to significant changes in the understanding of the established principles, rights and freedoms. The implementation of the agencies of constitutional control and the practical activities of these agencies indicate about significant changes in the understanding of the established principles, rights and freedoms. It should be noted quite a concise list of duties of citizens in these states. At the same time, the duty to observe public order and respect for public morality more closely concerns the respect for the principles of Islam as the state religion and the basis of legislation. Only in the Basic Nizami of Saudi Arabia contains a categorical provision on the practice of Islam and, in fact, it is not permitted to spread another religion. However, the constitutions of other monarchies of this region guarantee freedom of religion.

На основе действующих конституций монархий Арабского Востока и политико-правовой практики продемонстрированы особенности закрепления прав, свобод и обязанностей граждан (подданных). Сделан вывод о том, что конституционный статус личности в этих государствах только формально выглядит существенно модернизированным и демократизированным, однако фактически таким не является. В то же время приведены примеры деятельности органов конституционной юстиции, свидетельствующие о существенных изменениях в понимании закреплённых принципов, прав и свобод.
Features of the constitutional status of a person in Monarchies of the Arab East
Особенности конституционного статуса личности в монархиях Арабского Востока
Гришко, Л. М. Особливості конституційного статусу особи в монархіях Арабського Сходу / Л. М. Гришко // Право і безпека. – 2017. – № 3 (66). – С. 21-26.
Gryshko, L.M. (2017), “Features of the constitutional status of a person in monarchies of the Arab East” [“Osoblyvosti konstytutsiinoho statusu osoby v monarkhiiakh Arabskoho Skhodu”], Pravo i Bezpeka, No. 3, pp. 21–26.
Keywords: Конституційне право. Constitutional Law. Конституционное право; Наукові публікації. Scientific publications. Научные публикации; зарубіжний досвід; зарубежный опыт; foreign experience; монархії Арабського Сходу; Арабський Схід; арабские страны; Arab Monarchies of the East; конституційні принципи; правий статус особи; права та свободи громадян; обов’язки громадян; ісламська концепція прав людини; західна концепція прав людини; концепція прав людини; constitutional principles; legal status of a person; rights and freedoms of citizens; duties of citizens; Islamic concept of human rights; Western concept of human rights; конституционные принципы; правовой статус личности; права и свободы граждан; обязанности граждан; исламская концепция прав человека; западная концепция прав человека; концепция прав человека